Citizen Project Based on Problem Solving Skills - Sinaga, Osberth; Saragi, Daulat; Halking, Halking; Setiawan, Deny (Randwick International of Education and Linguistics Science Journal, 2024)
This study aims to develop a citizen project design based on problem-solving skills in the General Citizenship Course. The research method used is the R&D method following the Borg & Gall procedure. The research subjects involved: lecturers in charge of the Citizenship course; students as subjects for limited group trials; and four experts for validation of the citizen project practice design. The instrument used was an expert validation questionnaire which was analyzed using the Percentage of Average Score (PRS). Meanwhile, data analysis related to students' abilities in problem-solving skills was carried out using qualitative descriptive analysis techniques on the results of observations. The results of the study showed that the citizen project design based on problem-solving skills was declared valid and feasible to be used in Citizenship learning. The results also showed that the citizen project design can improve students' skills in solving problems, which include: critical thinking and problem-solving skills, communication and collaboration skills, contextual learning skills, and creation and renewal skills.